Life-Cycle Worker Flows and Cross-Country Differences in Aggregate Employment - Jonathan Créchet; Etienne Lalé; Linas Tarasonis (Institute of Labor Economics (IZA), 2024)
Cross-country employment differences are concentrated among women, the youth, and older individuals. In this paper, we document how worker flows between employment, unemployment, and out of the labor force vary by gender and age and contribute to aggregate employment differences across a large panel of European countries. We then build a life-cycle Diamond-Mortensen-Pissarides model capturing the salient features of our data. Key elements of the model are an extensive margin (i.e., labor force participation) and intensive margin (i.e., variable intensity) of search effort. The model attributes a major role to the production technology in driving differences in aggregate employment, while labor-market policies play a minor role. Search effort substantially amplifies the effects of technology across gender and age groups and is a prominent proximate cause of the cross-country variation in aggregate employment.
Keywords: E02; E24; J21; J64; J82; 330; employment; unemployment; labor force participation; life cycle; worker flows; labor market institutions